Model Pertumbuhan Polinomial Tanaman Meranti (Shorea spp) pada Sistem Tebang Pilih Tanam Jalur di PT Sari Bumi Kusuma - Endah Winarni; Wahyudi Wahyudi; Bhayu Rhama (HUTAN TROPIKA, 2023)
Meranti (Shorea spp) is a commercial trees that dominates the lowland tropical rainforests of Indonesia. Harvesting of this species has been carried out since the early 70's until now, but efforts to cultivate meranti are still very few. The silvicultural system of TPTJ with silin technique has placed meranti as species that must be planted by companies of forest concession. This study aims to construct a polynomial growth model for meranti at PT Sari Bumi Kusuma, so as to be able to predict the achievement of diameter, branch-free height and total height of meranti plants at a certain time. Meranti plants at PT Sari Bumi Kusuma have a diameter growth model: Y= 0.6076 + 0.3067X + 0.0524X2 (R2 : 94.74%), a branch-free height growth model: Y=0.0315+0.4787X+ 0.0081X2 (R2 : 89.53 %) and total height growth model: Y=0.4957+0.758X+0.0138X2 (R2 : 93.78%). The TPTJ system has a cutting cycle of 25 years with a limited diameter of harvested trees is 40 cm. Based on the results of this modeling, most of these trees have reached a diameter of 41.03 cm; branch-free height of 17.06 m and a total height of 28.07 m, so that it is ready to be harvested at the age of 25 years